PHILOSOPHICAL ESSENCE AND HISTORICAL-PHILOSOPHICAL SENSE OF PROTAGORAS’ THESIS - Александрова, А. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Article focuses on the problem of correctness of interpretation of philosophical texts in the historico-philosophical space.